Transformation of the social-economic and political values in Ukraine to the European Union values - Nosova, O. (Bulletin of V. N. Karazin Kharkiv National University Economic Series, 2022)
The article aims to analyze basic value approaches and define the main and decisive factors of values transformation. The research methods include descriptive analysis, institutional approach, and economic and statistical methods. The hypothesis of the study is to study how public perceptions have changed in extreme conditions (military conflict) towards European integration values. The broad scope of economic and sociological works reveals the necessity of a special analysis of the European integration and regional values adaptation in Ukraine and defines the problem for study, use, and dissemination of knowledge of the European Union values. The analysis of various value theories identifies the urgency and necessity of human behavior from the human value estimation study. We estimate how economic development depends on economic, political, and social values transformation and the overall indicators (market and democracy) reforms in Ukraine. We apply data from surveys to the comparing the population’s attitude toward European values since Ukrainian independence. The designation of core values allows formulating a strategy and intensifying a more sustainable strategy of political and social-economic development.